Occupational and environmental exposures in the Genomic Research in Alpha-1 Antitrypsin Deficiency and Sarcoidosis (GRADS) study. (August 2022) - Ryan, Sarah M.; Mroz, Margaret M.; Herzog, Erica L.; Ryu, Changwan; Fingerlin, Tasha E.; Maier, Lisa A.; Gulati, Mridu
Abstract: Introduction: Sarcoidosis is a granulomatous disorder thought to be caused by exposures in genetically susceptible individuals. This study investigated whether specific exposures were associated with different sarcoidosis phenotypes. Methods: Extensive demographic, occupational and environmental exposure data was analyzed from subjects enrolled in the NHLBI Genomic Research in Alpha-1 Antitrypsin Deficiency and Sarcoidosis (GRADS) study. Results: In patients with sarcoidosis, radiation exposure was significantly associated with an increased risk of cardiac sarcoidosis versus non-cardiac sarcoidosis. No exposures were significantly associated with pulmonary only disease versus extrapulmonary disease with or without pulmonary involvement, Scadding Stage II/III/IV versus Scadding Stage 0/I, acute or remitting disease versus non-acute or non-remitting disease, nor chronic versus non-chronic disease. Although not reaching statistically significance after adjustment for multiple comparisons, there were a number of exposures associated with specific disease phenotypes, including exposures where relationships to sarcoidosis have previously been described such as rural exposures and pesticide exposures. Conclusions: Radiation exposure may be a risk factor for cardiac sarcoidosis. Other exposures may also be associated with specific phenotypes and should be further explored. The study was limited by small groups of exposed subjects for individual exposures and multiple comparisons. The development of novel and innovative exposure assessment tools is needed.